2015
DOI: 10.1007/s11356-015-5105-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Beauveria bassiana infection on cell mediated and humoral immune response in house fly, Musca domestica L.

Abstract: Entomopathogenic fungi that manifest infections by overcoming insect's immune response could be a successful control agent for the house fly, Musca domestica L. which is a major domestic, medical, and veterinary pest. In this study, the immune response of house fly to Beauveria bassiana infection was investigated to reveal fundamental aspects of house fly hemocyte biology, such as hemocyte numbers and size, which is poorly understood. The total hemocyte counts (THCs) in B. bassiana-infected house fly showed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Hence, it is not surprising to see that parasitoids and entomopathogenic fungi evolved mechanisms to specifically suppress hemocytic immune functions of their hosts. Several fungal species increase host THC after infection (Mishra, Kumar, & Malik, ; Sewify & Hashem, ) and other studies report that the THC of host insects decreases after fungal infection (Avulova & Rosengaus, ; Bandani, ). Decreasing the THC may led to cellular immunosuppression, which would favor the infecting fungus.…”
Section: Discussionmentioning
confidence: 96%
“…Hence, it is not surprising to see that parasitoids and entomopathogenic fungi evolved mechanisms to specifically suppress hemocytic immune functions of their hosts. Several fungal species increase host THC after infection (Mishra, Kumar, & Malik, ; Sewify & Hashem, ) and other studies report that the THC of host insects decreases after fungal infection (Avulova & Rosengaus, ; Bandani, ). Decreasing the THC may led to cellular immunosuppression, which would favor the infecting fungus.…”
Section: Discussionmentioning
confidence: 96%
“…In Locusta migratoria, the hemocytes and hematopoietic tissue mutually assist each other to clear invading pathogens from the circulation (Duressa et al 2015). In housefly, hemocyte number varied during fungal infection (Mishra et al 2015). According to these results, we infer that because a great deal of fungal spores was injected into the coelom of housefly larvae, a fraction was transported to the gaps of tissues.…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that housefly larvae were prone to induce the generation of AMPs such as attacin, cecropin, defensin and diptericin by means of heat shock, ultraviolet exposure and needle piercing Liang et al 2006;Dang et al 2010;Liu et al 2011). Once the adult housefly is infected with Beauveria bassiana, hemocyte density changes and fungi number in the hemolymph are synchronized (Mishra et al 2015). The published genome sequences analysis of housefly indicated that compared with Drosophila melanogaster, the genome contains a rich resource of shared and novel protein coding genes, a significantly higher amount of repetitive elements, and substantial increases in copy number and diversity of both the recognition and effector components of the immune system, including a large number of genes encoding PAMPs, immunerelated signalling pathways, immune effector molecules and antimicrobial peptides (Scott et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign cells in the hemocel activated systemic immune mechanisms, which consisted of cellular and humoral immunity (Lemaitre and Hoffmann, 2007;Jiangfan et al, 2016). Hemocytes being precursor of innate immunity in insects, a strong correlation between hemocyte number and immune response (Mishra et al, 2015). Parasitoid wasp infection in D. melanogaster induces a number of significant increases in total hemocytes (Russo et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Parasitoid wasp infection in D. melanogaster induces a number of significant increases in total hemocytes (Russo et al, 2001). Considerable variations in the relative densities of various hemocyte in the infected house flies indicated stress development during infection (Mishra et al, 2015). The stress developed in hemocyte indicated the change in immunity (Ribeiro and Brehélin, 2006).…”
Section: Introductionmentioning
confidence: 99%